Structural Deformation to β‐Cyclodextrin Due to Strong π‐Stacking in the Self‐Assembly of Inclusion Complex. Issue 47 (14th December 2020) - Jeevan, Athira K.; Krishnan, Sumesh B.; Gopidas, Karical R.
Abstract: We report severe distortion to the structure of β‐cyclodextrin and partial de‐encapsulation of included guest prompted by strong π‐stacking of appended pyrene moieties in the self‐assembly of inclusion complex into toroidal nanostructures. The inclusion complex formed from bis(β‐cyclodextrin)‐substituted pyrene and bis(adamantane)‐substituted methyl viologen assembled into ring‐like structures. The rings undergo further self‐assembly which involve strong face‐to‐face π‐stacking of pyrene chromophores. Close approach of the pyrenes for π‐stacking demands severe distortion of the cyclodextrin truncated cone structure and partial de‐encapsulation of the guest from the cavity. The understanding that β‐CD can be distorted severely during self‐assembly may be helpful in the design of molecular architectures. Abstract : Bis(β‐cyclodextrin)‐substituted pyrene and bis(adamantane)‐substituted methyl viologen assembled into toroidal nanostructures in aqueous solution. The toroids are formed by self‐assembly of initially formed inclusion complex into ring‐like structures and stacking of the ring‐structures. Ring stacking occurs through face‐to‐face stacking of pyrenes which demands partial de‐encapsulation of the adamantane guests from the cavity and severe distortion of the β‐cyclodextrin truncated cone structure.